Centenarian caregivers: perception of burden, sociodemographic data and physical activity - Giovana Zarpellon Mazo; Daliana Stephanie Lecuona; Francine Stein; Fabíola Aguiar de Souza; Íris Dantas da Mota; Priscila Rodrigues Gil; Damiana Lima Costa; Pedro Silvelo Franco (Acta Scientiarum. Health Sciences, 2022)
This study aimed to understand centenarian caregivers’ perception of care burden according to sociodemographic characteristics and physical activity level. This is a descriptive study that used a mixed data (quantitative and qualitative) approach. Sixty-seven caregivers of centenarians from municipalities in Santa Catarina participated in this study. Interviews were held for application of questions about sociodemographic data, transport-related and leisure-time physical activity, caregiver burden, and suggestions for improving care. The data were collected in the centenarian’s home where the caregiver worked. Quantitative data were analyzed using descriptive and inferential statistics and qualitative data by content analysis. The results showed that 58.2% of the caregivers were overburdened. Of these, 92.3% were females, 56.4% were 60-75 years old, 48.7% had 7 to 11 years of schooling, 53.8% were married, 66.7% were children of centenarians, the caregiving duration ranged from 1 to 5 years in 35.9%, and 69.2% cared for the older adult 24 hours/day. There was a statistically significant difference (p = 0.01) between the level of leisure-time physical activity and caregiving burden, with 64.9% of insufficiently active caregivers tending to be overburdened with the care demand. The suggestions of caregivers for improving centenarian care included having help from health professionals and relatives for care, infrastructure, and financial resources. Most burdened caregivers are insufficiently active and need assistance in taking care of their own health.